STABILITY OF DRUG FORM OF PARACETAMOL, FORMED ON THE BASIS OF CRYSTALS OF ROMBIC MODIFICATION - A. P. Belyaev; V. P. Rubets; V. V. Antipov; E. Y. Rodionova (Разработка и регистрация лекарственных средств, 2019)
Drug form of paracetamol formed on the basis of molecular crystals of rhombic modification was studied. The studies included technological experiments, optical microscopy, differential scanning calorimetry, X-ray diffraction and IR spectroscopy. It is found that drug forms of paracetamol, synthesized by calorimetric method, together with enlarged solubility possess remarkable sensibility to temperature and mechanic grinding. It is presented X-ray patterns, IR spectra and curves of differential scanning calorimetry.